2021
DOI: 10.1177/0391398821995503
|View full text |Cite
|
Sign up to set email alerts
|

Changes in extracellular water with hemodialysis and fall in systolic blood pressure

Abstract: Introduction: Intra-dialytic hypotension (IDH) remains the most common complication with outpatient hemodialysis (HD) sessions. As fluid is removed during HD, there is contraction of the extracellular volume (ECW). We wished to determine whether the fall in ECW was associated with a fall in systolic blood pressure (SBP). Methods: We retrospectively reviewed the records of adult dialysis outpatients attending for their midweek sessions who had corresponding pre- and post-HD bioimpedance measurements of ECW. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Understanding the optimal fluid volume balance will facilitate the clinical application of body fluid assessment methods. A recent study revealed an association between the reduction in ECW and systolic blood pressure (SBP) with dialysis, and researchers advocated monitoring changes in ECW during dialysis to reduce the risk of intradialytic hypotension ( 53 ). This study showed that the TBW, ICW, and ECW values in females increased first and then decreased thereafter during the lifetime, with peak values appearing in the 41~ group.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the optimal fluid volume balance will facilitate the clinical application of body fluid assessment methods. A recent study revealed an association between the reduction in ECW and systolic blood pressure (SBP) with dialysis, and researchers advocated monitoring changes in ECW during dialysis to reduce the risk of intradialytic hypotension ( 53 ). This study showed that the TBW, ICW, and ECW values in females increased first and then decreased thereafter during the lifetime, with peak values appearing in the 41~ group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the body water, including total body water, intracellular water and extracellular water are positively correlated with blood pressure in different patients, including those with chronic kidney disease [ 33 ], those on hemodialysis and those with primary hypertension [ 34 , 35 ]. Blood pressure is sensitive to extracellular body water; extracellular water overhydration was significantly greater in patients whose blood pressures increased post dialysis [ 36 , 37 ]. We also found that the association between decreased blood pressure and reduced extracellular body water in DASH + TRE group.…”
Section: Discussionmentioning
confidence: 99%
“…The "dry weight" assessment-based approach, although necessary from a clinical perspective and unquestionably beneficial toward improving CV outcomes is cumbersome and difficult to apply in daily routine, has been conceptually challenged and incurs additional costs [28,46,[99][100][101]. More objective and precise approaches that rely on biomarkers and automated technical tools to support clinical decision-making for sodium, fluid, and BP managements are therefore needed [102].…”
Section: Strategies and Tools To Mitigate The Sodium-fluid Overload I...mentioning
confidence: 99%